Facebook Tiktok and Instagram as a Marketing Tools and Branding Strategy for MSMEs - Wulandari , Citra Mayu; Helmi, Sulaiman; Gunarto, Muji; Zinaida, Rahma Santhi (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the social media performance of Pempek Sulthan and Pindang Agan Palembang on Instagram and TikTok platforms and evaluate the effectiveness of each platform in the context of MSME marketing and branding. Data were collected from the analysis of impressions, engagement rates, and follower growth over a certain period. The results show that TikTok generates a higher average daily impression than Instagram, with 833 impressions per day and 86% new followers, while Instagram records 499 impressions per day and 53% new followers. However, the engagement rate on both platforms is still low, below 1, indicating minimal follower engagement. In terms of growth performance, Instagram is superior in likes, comments, and views metrics compared to TikTok, although this comparison is influenced by the higher frequency of posting on Instagram. The SWOT analysis identifies the position of Pempek Sulthan and Pindang Agan in Quadrant I, indicating strength and readiness for expansion through a vertical integration strategy. The QSPM results emphasize the importance of monitoring platform performance to evaluate marketing effectiveness and determine future platform usage strategies.